Lower electronic health record adoption and interoperability in rural versus urban physician participants: a cross-sectional analysis from the CMS quality payment program - A. Jerrod Anzalone; Carol R. Geary; Ran Dai; Shinobu Watanabe-Galloway; James C. McClay; James R. Campbell (BMC Health Services Research)
Abstract Background The Health Information Technology for Economic and Clinical Health Act of 2009 introduced the Meaningful Use program to incentivize the adoption of electronic health records (EHRs) in the U.S. This study investigates the disparities in EHR adoption and interoperability between rural and urban physicians in the context of federal programs like the Medicare Access and CHIP Reauthorization Act of 2015 and the 21st Century Cures Act. Methods A cross-sectional analysis was conducted using the 2021 Quality Payment Program Experience Report Public Use File to compare EHR adoption and Promoting Interoperability scores (PISs) between urban and rural physician participants. Data were linked with the Certified Health IT Product List to assess certified EHR adoption and interoperability. Results The study included 209,152 physician participants, 12% of whom practiced in rural communities. EHR adoption was significantly higher in urban (74%) than in rural areas (64%). Epic Systems dominated the market in both settings. Multivariable logistic regression indicated lower odds of EHR adoption among rural physicians (OR: 0.79, CI: 0.76–0.82). Rural physicians also had lower PISs (β: –3.5, CI: –4.1 to –3.0). Factors like extreme hardship, small practitioner status, and location in a health professional shortage area significantly impacted EHR adoption and PISs. Conclusions Significant disparities exist in EHR adoption and interoperability between rural and urban physicians. These disparities highlight the need for targeted interventions to enhance EHR adoption and interoperability in rural settings to ensure equitable access to healthcare technologies and improved patient outcomes across all communities.